2011
DOI: 10.1080/09593330.2010.517220
|View full text |Cite
|
Sign up to set email alerts
|

Biofouling characteristics and identification of preponderant bacteria at different nutrient levels in batch tests of a recirculating cooling water system

Abstract: Understanding the influence of nutrient levels on biofouling control is an important requirement for management strategies in a recirculating cooling water system. Nutrient limitation may be one way to control biofouling development without increasing biocide dosing. Therefore, this study was carried out to investigate the effects of nutrient levels on biofouling characteristics and to identify the preponderant bacteria in the batch tests with a simulated cooling water system. The biofouling characteristics we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…In recent years, more attention has been paid to the reuse of refinery wastewater in the petroleum industry after advanced treatment (Liu et al, 2011a(Liu et al, , 2011b. Compared with natural water, there are a considerable number of inorganic ions and organic substrates in refinery wastewater, which would lead to easier scale formation in circulating cooling water systems (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more attention has been paid to the reuse of refinery wastewater in the petroleum industry after advanced treatment (Liu et al, 2011a(Liu et al, , 2011b. Compared with natural water, there are a considerable number of inorganic ions and organic substrates in refinery wastewater, which would lead to easier scale formation in circulating cooling water systems (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, when supplementing the sample (66 mL) with 25 mL 1M glucose and a 25 mL LB medium, the respiration rate increased by around three times (from 1.16 to 3.80 µmol/L/h). This implies that the respiration rate within cooling water is limited and influenced by the available nutrients, as has also been shown in a previous study [37]. If the reservoir water samples are not supplemented with micro-and macro-nutrients, the measurements would be biased toward the specific water matrix present at the time point of sampling.…”
Section: Oxygen Respiration Measurementsmentioning
confidence: 65%
“…Furthermore, it is possible to tune the sensitivity of the sensor by other means, such as using a different matrix polymer as shown in a previous study [41]. Nevertheless, as oxygen consumption can clearly be correlated with bacterial load; this makes it possible to assess the amount of bacteria within a sample with a measurement time of around 30 min [37]. This is a significant reduction of the time between sampling and analysis, compared to the current 48 h taken by cultivation-based methods.…”
Section: Oxygen Respiration Measurementsmentioning
confidence: 99%
“…At the high substrate level, more substrates inhibited the contact between biocides and microorganism and so resulted in reducing QAC antimicrobial efficiency (Wäsche et al 2004). Sundheim et al showed that some kind microorganisms produced resistance to QAC (Sundheim et al 1998), and there were difference of preponderant bacteria in biofilms at different nutrient levels (Liu et al 2010). These factors all affect BDMDAC MIT.…”
Section: Antimicrobial Effect Of Bdmdac On Biofilmmentioning
confidence: 98%